(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The nation’s prosperity and happiness lies in the health of its citizens. Good health is a fundamental human right, and each country is responsible for the provision of adequate health facilities for its population, since health and development are closely inter-twined and inseparable aspects of the government. Promotion of health is essential for national progress.Health contributes to a better quality of life and World peace. The health of a nation is not only an essential component to the nation’s economic growth but also for internal stability. Assuring a minimal level of health care to the population is a critical constituent of the development process. Hospitals and health centers play a vital role in protection of health of the people. Good health delivery is always associated with better capability and leadership.